Temporal Variability of Sea Surface Temperature in Iraq Marine Water, Northwest of Arabian Gulf. - Lafta, Ali Abdulridha; Abdullah, Sadiq Salim (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Understanding sea surface temperature (SST) Changes in coastal areas is crucial for many aspects of the coastal environment and maritime operations in these water systems. Although SST fluctuations have been frequently documented in various Arabian Gulf areas, such variations in Iraq's marine waters, situated northwest of the Arabian Gulf, are poorly understood. To determine the temporal variations of SST, we examined SST measurements taken off the coast of Iraq between 2017 and 2019. The results revealed that SST exhibited pronounced annual, semiannual, and seasonal fluctuations. The highest and lowest recorded SST values were 36.77 and 14.68  ͦ C, respectively. The seasonal averages of SST reach their maximum value during the summer season at 32.38 C and then are reduced to their lowest range during winter at 17.23 C. Furthermore, the results revealed that the highest SST was recorded in August of all three study years, namely 2017, 2018, and 2019. Meanwhile, the lowest recorded SST was observed in December of 2017 and February of both 2018 and 2019. The results also revealed a negative correlation between SST and Shamal winds. A perceived decrease in SST occurs with Shamal wind events, where the average reduction of SST reaches 2-3 C. At the same time, our results show that SST increases when the southeast wind is predominant. The results obtained in this study could be beneficial for several aspects of the environmental and maritime at this significant part of the Arabian Gulf.